Kreativitas Sebagai Strategi Pengembangan Musik Kompang Grup Delima di Bantan Tua Bengkalis - Rosta Minawati; Nursyirwan Nursyirwan (PANGGUNG, 2018)
ABSTRACTThis article aims to discover the strategy of creativity used by performers of Kompang music in Bantan Tua, Bengkalis. The data was collected through observation, interviews, and documentation. The Kompang Delima Group is one of the kompang groups that has developed kompang as performing art. In 2012 the Delima Group started to include creative movements in their performances. The movement creativities were inspired by the social and cultural life of the people. “Nunduk” is one of the characteristic movements of the Delima Group in Bantan inspired by menoreh (harvesting a rubber). The creativities are developed through the elements of local culture, including movements, formations, and floor patterns, and the emphasis on the clarity of articulation in each line of the recitation of the barzanzi text in order to gain more aesthetic impression of performance.Keywords: creativity, Kompang music, Delima group, BengkalisABSTRAKTulisan ini bertujuan mengungkap strategi kreativitas pemain musik Kompang di Bantan Tua Bengkalis. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Grup Kompang Delima adalah salah satu grup Kompang yang mengembangkan musik Kompang sebagai seni pertunjukan. Pada tahun 2012, Grup Delima mulai memasukkan gerak yang kreatif di dalam pertunjukannya. Hasil kreativitas yang dilakukan dengan menggarap gerak yang terinspirasi dari kehidupan sosial dan kultur masyarakatnya. Nunduk adalah gerakan yang khas yang dimiliki grup Delima di Bantan Tua yang terinspirasi dari menoreh (mengambil karet). Kreativitas dilakukan dengan mengembangkan gerak, formasi dan pola lantai, serta penekanan pada kejelasan artikulasi setiap syair barzanji yang dilafalkan agar tercapai kesan estetik dalam penampilannya.Kata kunci: kreativitas, musik Kompang, grup Delima, Bengkalis